Design of multi-haptenized dendrimeric-antigens for in vitro IgE recognition - Nájera-Albendín, Francisco; Montañez-Vega, María Isabel; Ruiz-Sanchez, Antonio Jesus; Vida-Pol, Yolanda; Collado-Martín, Daniel; Pérez-de-Inestrosa-Villatoro, Ezequiel; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa; Blanca Gómez, Miguel (My University, 2014)
Reactions mediated by the Immunoglobulin E (IgE) involved a high number of allergic drug responses, ranging from simple skin symptoms to anaphylactic shock.1 In order to emulate the recognition process working in vivo, much effort have been made to prepare hapten(drug)-carrier(protein) conjugates attempting to work like the antigen responsible for the allergic drug reaction.2 In our efforts to exploit the dendrimer properties in the interaction with the immunological system,3 we have prepared and characterized a series of G4-PAMAM dendrimers peripherally decorated with the determinant responsible of the allergic response to the β-lactam antibiotic: benzylpenicillin (BPO) or amoxicillin (AXO). Additionally, three multi-haptenized Dendrimeric-Antigens (DeAn) including both epitopes (BPO and AXO) in the same carrier have been prepared. The combination of 1D and 2D-NMR techniques and Molecular Dynamic simulations,4 allow the structural characterization of these new antigens and afford evidences that the composition and the distribution of both haptens on the dendrimer surface play key roles for the IgE-antigen recognition. The immunochemical studies of these DeAn enable to diagnose patients allergic to benzylpenicillin, amoxicillin or to both drugs with a single test. These DeAn provide a significant model to study IgE recognition from patients who suffer an allergic reaction to these -lactam antibiotics.
Comunicación Oral
Keywords: Química orgánica; Organic Chemistry; Dendrimer; IgE